2019
DOI: 10.1519/jsc.0000000000002016
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Movement Skills and Physical Qualities of Elite Senior and Academy Rugby League Players

Abstract: The aim of the present study was to investigate (a) the differences in the movement skills and physical qualities between academy and senior rugby league players, and (b) the relationships between movement skills and physical qualities. Fifty-five male rugby league players (Senior, n=18; Under 19 n=23; Under 16, n=14) undertook a physical testing battery including anthropometric (stature & body mass), strength (isometric mid-thigh pull; IMTP) and power (countermovement jump; CMJ) qualities, alongside the athle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 32 publications
4
29
3
1
Order By: Relevance
“…In contrast to the current study, a previous study of the English rugby league system, did find significant differences between junior groups (under 16 (U16) and under 19 (U19)) (12). Ireton et al (12), stated that the U19 group demonstrated superior athletic movement ability for push ups, single leg RDL and double lunge right compared to the U16 group (12). However, the only significant differences between groups were that the senior group performed right side lunge and right side RDL, better compared to U19 group (12).…”
Section: A C C E P T E Dcontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the current study, a previous study of the English rugby league system, did find significant differences between junior groups (under 16 (U16) and under 19 (U19)) (12). Ireton et al (12), stated that the U19 group demonstrated superior athletic movement ability for push ups, single leg RDL and double lunge right compared to the U16 group (12). However, the only significant differences between groups were that the senior group performed right side lunge and right side RDL, better compared to U19 group (12).…”
Section: A C C E P T E Dcontrasting
confidence: 99%
“…This may be due to SL players having both greater playing experience and exposure to athletic movement, strength programs and screenings by appropriately qualified professionals for longer periods wherein any weaknesses may have been addressed. In contrast to the current study, a previous study of the English rugby league system, did find significant differences between junior groups (under 16 (U16) and under 19 (U19)) (12). Ireton et al (12), stated that the U19 group demonstrated superior athletic movement ability for push ups, single leg RDL and double lunge right compared to the U16 group (12).…”
Section: A C C E P T E Dcontrasting
confidence: 90%
See 3 more Smart Citations